Problematika mengenai taukil wali bil kitabah di Kantor Urusan Agama (KUA) Kecamatan Klojen perspektif Kepala KUA - Setyawan, Prayoga Fajar (Maliki Interdisciplinary Journal, 2024)
This article discusses the problem of taukil wali bil kitabah at the Klojen KUA. The background in this study explains that there was a letter of agreement on taukil wali bil kitabah issued by the KUA concerned without facing each other between the wali nasab and the head of the local KUA which was ultimately rejected by the Head of the KUA Klojen sub-district. The purpose of this study is to dig deeper into the views and solutions of the head of the KUA Klojen in overcoming these problems. This research is included in the type of empirical legal research using a qualitative approach. The results showed that the head of the Klojen KUA was of the view that the taukil wali bil kitabah pledge letter could be used if the marriage guardian, the prospective bride and groom are dealing with the head of the local KUA or if the marriage guardian has an udzur, it can only be the bride and groom who are facing the head of the local KUA. The solution to this problem arose when the head of the KUA Klojen investigated more deeply about the lineage of the prospective bride and groom, who turned out to be in prison. Therefore, the head of the Klojen KUA advised the prospective bride and groom to contact the police at the prison to request a letter of proof that the family’s guardian could not be released from prison so that with this proof the marriage could take place.